Abdominal Stretching Exercise as A Complementary Therapy for Dysmenorrhea Pain in Adolescent Girls - Deswita Cahaya Dina; Sulastri Sulastri (Indonesian Journal of Global Health Research, 2026)
Dysmenorrhoea is a reproductive health problem commonly experienced by adolescent girls and women of reproductive age, with a high prevalence and significant impact on daily activities, emotional well-being, and quality of life. Physical exercise, particularly abdominal stretching exercises, has the potential to be a non-pharmacological intervention in attenuating the pain scale of dysmenorrhea through increased comfort and muscle relaxation. This study was conducted to determine the effect of abdominal stretching exercises on attenuating the pain scale of dysmenorrhea at SMA Negeri 2 Sukoharjo. This study used a quantitative method with a one-group pretest–posttest quasi-experimental design. The study was conducted in September 2025 on 87 female students in grade XI at SMA N 2 Sukoharjo who were selected using purposive sampling according to the inclusion criteria. The intervention given was abdominal stretching exercises. The severity level of dysmenorrhea pain was assessed pre- and post-intervention employing the Numeric Rating Scale (NRS). Data analysis included univariate and bivariate analyses. Normality was tested using Kolmogorov–Smirnov and showed that the data were not normally distributed, so bivariate analysis used the Wilcoxon signed rank test with a confidence level of 95% and α = 0.05. The results showed that the majority of respondents were 16 years old with a dominant age of menarche of 12 years and had a normal menstrual cycle and duration. Before the intervention, most respondents experienced moderate dysmenorrhea pain (scale 5). After being given abdominal stretching exercises, there was a decrease in the intensity of dysmenorrhea pain, with the majority of respondents experiencing low pain (scale 2). Bivariate analysis using the Wilcoxon signed rank test showed a significant difference between the pain scale before and after the intervention (p ≤ 0.05), indicating that abdominal stretching exercises are effective in reducing the scale of dysmenorrhea pain. This study shows that abdominal stretching exercises are effective in reducing the pain scale of dysmenorrhoea in adolescent girls.